Yenny Saraswati ANALISIS DESIGN LONG STORAGE PADA EMBUNG SUMBER PULE DENGAN METODE PASTEN MODIFIKASI - Yenny Saraswati; Nur janah (Universitas Islam Balitar Blitar, 2020)
Embung Sumber Pule is a long-standing water reserve located in the village of Purworejo, Kandat District, Kediri Regency. Embung is a small-scale water building (reservoir) around agricultural land that was built to absorb the amount of rainwater in the rainy season to meet the water quality criteria. Long Storage is a water-holding building used to store water in rivers, canals and / or ditches on relatively flat land. The current situation in the reservoir of pule has problems of reduction of water resources. The first step of this research is the hydrological analysis to determine the monthly precipitation, the actual precipitation R80, the actual rainfall 15 days. The results of the analysis are then used to calculate the water requirements using Pâten'satau the Pasten method and the planning of the reservoir design of the pule source. Based on the analysis and design of the tank, the dimensions of the tank are 2 m high, 72.5 m wide, round headlight type, 1 rinsing door with a size (2.42 mx 1, 16 m), water tank of 381,338 m3, foundation depth 0, 8 m, foundation volume of 0,308 m3 able to support a load of 0,462 ton.